Nuevas fuentes para el análisis del transporte internacional de mercancías a través de los Pirineos - Escalona Orcao, Ana Isabel; Andrés Visus, Victor (Geographicalia, 2017)
This article introduces a new source for the analysis of commoditys transport across the Pyrenees, which is the data base of the Dirección General de Tráfico, concerning entries and exits of vehicles through 13 border points between France and Spain. The results for 1997 show that current traffic pattern is reaching insostenibility and that alternative patterns, relying on railways and through the central section of Pyrenees, must be promoted.